2016
DOI: 10.1002/rcm.7553
|View full text |Cite
|
Sign up to set email alerts
|

Abundance correction for mass discrimination effects in polymer mass spectra

Abstract: Our computational method may help to avoid erroneous conclusions when analyzing copolymer MS spectra. The software is freely available and represents a step towards comprehensive computational support in polymer science. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Using mixtures of peptides, synthetic polymers and lipids, the authors showed the detection of analyte ions that had been suppressed with the traditional dry-drop method. Mass discrimination has always been a serious problem in MALDI-TOF MS. Engler et al devised a free module for COCONUT software to overcome mass discrimination when analyzing polymers . The authors illustrate the improvements of applying the software to spectra of three different styrene/isoprene copolymers, as well as their corresponding homopolymers.…”
Section: Traditional Ionization Methods For Msmentioning
confidence: 55%
See 1 more Smart Citation
“…Using mixtures of peptides, synthetic polymers and lipids, the authors showed the detection of analyte ions that had been suppressed with the traditional dry-drop method. Mass discrimination has always been a serious problem in MALDI-TOF MS. Engler et al devised a free module for COCONUT software to overcome mass discrimination when analyzing polymers . The authors illustrate the improvements of applying the software to spectra of three different styrene/isoprene copolymers, as well as their corresponding homopolymers.…”
Section: Traditional Ionization Methods For Msmentioning
confidence: 55%
“…Mass discrimination has always been a serious problem in MALDI-TOF MS. Engler et al devised a free module for COCONUT software to overcome mass discrimination when analyzing polymers. 149 The authors illustrate the improvements of applying the software to spectra of three different styrene/isoprene copolymers, as well as their corresponding homopolymers. Lu et al measured the ion-toneutral ratios of four common MALDI matrixes at 355 nm using a TOF-MS. 150 These authors noted that the ion-toneutral ratios are similar to those predicted by the thermal proton transfer model.…”
Section: ■ Traditional Ionization Methods For Msmentioning
confidence: 99%
“…Our model allows for computing the likelihood of a single polymer chain [24]. Let S be a sequence (polymer chain) and H a hypothesis, i.e., the geometric model.…”
Section: Methodsmentioning
confidence: 99%
“…This mass discrimination in MALDI MS has been found to underestimate the polymer molecules of higher mass. [22][23][24] Thermal analysis…”
Section: Click Polymerizationmentioning
confidence: 99%